Novel methods to identify and measure catabolism. Issue 4 (August 2021) - Page, Alexandria; Flower, Luke; Prowle, John; Puthucheary, Zudin
Abstract : Purpose of review: Assess current potential catabolism-biomarkers to characterize patients developing prolonged critical illness. Recent findings: A raised urea-to-creatinine ratio (UCR) during critical illness is negatively associated with muscle mass with greater increases in UCR seen patients developing persistent critical illness. Similarly, sarcopenia index (a ratio of creatinine to cystatin-c concentrations) correlates well to muscle mass in intensive care populations. Elevated growth/differentiation factor-15 (GDF-15) has been inconsistently associated with muscle loss. Although GDF-15 was a poor marker of feeding tolerance, it has been associated with worse prognosis in intensive care. Summary: UCR is an available and clinically applicable biomarker of catabolism. Similarly, sarcopenia index can be used to assess muscle mass and indirectly measure catabolism based on readily available biochemical measurements. The utility of novel biomarkers, such as GDF-15 is less established.